2018
DOI: 10.1002/advs.201800793
|View full text |Cite
|
Sign up to set email alerts
|

Management of Crystallization Kinetics for Efficient and Stable Low‐Dimensional Ruddlesden–Popper (LDRP) Lead‐Free Perovskite Solar Cells

Abstract: Low‐dimensional Ruddlesden–Popper (LDRP) lead‐free perovskite has great potential due to its improved stability and oriented crystal growth, which is mainly attributed to the effective control of crystallization kinetics. However, the crystallization kinetics of LDRP lead‐free perovskite films are highly limited by Lewis theory. Here, the management of the crystallization kinetics of LDRP tin (Sn) perovskite films jointly controlled by Lewis adducts and the ion exchange process using a mixture of polar aprotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 42 publications
(115 reference statements)
3
106
0
Order By: Relevance
“…Later, Qiu et al reported for the first time the crystallization kinetics management of RP tin‐based perovskites controlled by Lewis adducts and ion exchange processes. [ 117 ] As a result, they obtained a film with a good average grain size of ≈9 µm; the best PCE was at 4.03%. It showed good stability and was placed in a nitrogen atmosphere for 94 d without degradation.…”
Section: Strategies For Improving Stabilitymentioning
confidence: 99%
“…Later, Qiu et al reported for the first time the crystallization kinetics management of RP tin‐based perovskites controlled by Lewis adducts and ion exchange processes. [ 117 ] As a result, they obtained a film with a good average grain size of ≈9 µm; the best PCE was at 4.03%. It showed good stability and was placed in a nitrogen atmosphere for 94 d without degradation.…”
Section: Strategies For Improving Stabilitymentioning
confidence: 99%
“…The structure of the 2D layered perovskites is defined by the general formula A 2 A′ n − 1 M n X 3 n + 1 or AA′ n − 1 M n X 3 n + 1 , wherein the former, having monoammonium spacer cations, is named the Ruddlesden–Popper (RP) phase, and the latter, with diammonium spacer cations, is called the Dion–Jacobson (DJ) phase . At present, the research on RP phase perovskites is relatively mature, and various methods have been used to control crystal orientation and QW distribution, which are two critical factors influencing the performance. Hot casting was first reported to achieve vertical orientation, followed by the use of additives, shorter spacers, and the introduction of small amounts of FA + and Cs + .…”
Section: Comparison Of Champion Photovoltaic Performance Of Pda‐ Bdamentioning
confidence: 99%
“…The bandgaps can be tuned from 1.20 ( n = ∞) to 1.83 eV ( n = 1), whereas the CBMs are lifted too high to match with one of the TiO 2 . Qiu et al further optimized the crystallization kinetics of (BA) 2 (MA) n −1 Sn n I 3 n +1 and obtained uniform films with a grain size close to 9 μm . DMSO/methylammonium acetate (MAAc) were used as the mixed‐solvent and the crystallization undergoes an Ac − –I − ion‐exchange process.…”
Section: Strategies For High Performancementioning
confidence: 99%